Measuring for change: A multi-centre pre-post trial of an air quality feedback intervention to promote smoke-free homes - Ruaraidh Dobson; Rachel O'Donnell; Olena Tigova; Marcela Fu; Marta Enríquez; Esteve Fernandez; Giulia Carreras; Giuseppe Gorini; Simona Verdi; Alessandro Borgini; Andrea Tittarelli; Chiara Veronese; et al. (Environment International, 2020)
Introduction: Second-hand smoke exposure in the home is a serious cause of ill-health for children. Behaviour change interventions have been developed to encourage parents to keep homes smoke-free. This study evaluates a novel air quality feedback intervention using remote air quality monitoring with SMS and email messaging to promote smoke-free homes among families from deprived areas. Methods: This paper presents a pre-post study of this intervention. Using internet connected monitors developed with the Dylos DC1700, daily SMS and weekly email feedback provided for 16 days to participants recruited in four European countries. Participants were recruited based on their stage of change, in order to target those most able to achieve smoke-free homes. The primary outcome measure was median change in mean fine particulate matter (PM2.5) concentration between baseline and follow-up periods, while secondary outcome measures included change in time over the World Health Organisation (WHO) guideline limit for PM2.5 exposure over 24 h (25 µg/m3) in those periods and the number of homes where PM2.5 concentrations reduced. Telephone interviews were conducted with participants in Scotland post-intervention to explore intervention experience and perceived effectiveness. Results: Of 86 homes that completed the intervention study, 57 (66%) experienced pre-post reductions in measured PM2.5. The median reduction experienced was 4.1 µg/m3 (a reduction of 19% from baseline, p = 0.008). Eight homes where concentrations were higher than the WHO guideline limit at baseline fell below that level at follow-up. In follow-up interviews, participants expressed positive views on the usefulness of air quality feedback. Discussion: Household air quality monitoring with SMS and email feedback can lead to behaviour change and consequent reductions in SHS in homes, but within the context of our study few homes became totally smoke-free.